2001
DOI: 10.1007/s007870170024
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported strengths and difficulties in a community sample of Finnish adolescents

Abstract: The psychometric properties of the self-report version of the Strengths and Difficulties Questionnaire (SDQ) among Finnish 13- to 17-year-old adolescents (n = 1,458) were studied. The results show that the psychometric properties of the Finnish SDQ self-report were adequate. The results of the correlation analysis confirmed the postulated structure of the SDQ self-report. The correlations of the items to their respective subscales ranged from moderate to high (r = 0.47-0.73). The internal consistency was accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
102
5
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(148 citation statements)
references
References 12 publications
29
102
5
11
Order By: Relevance
“…The respective models based on the three-factor structure with the correlated errors added, and with the reverse-worded items allowed to cross-load on the Prosocial dimension, displayed all of them lower fit indices than their correlated five-factor models. As so, the three-factor structure of the SDQ was found not adequate, similarly to the findings in previous studies [40,56,32,11]. Regarding this, ΔCFI analysis revealed that, contrary to van de Looij-Jansen et al [26], both in the three and the five-factor models, the inclusion of modifications is more significant in model fit than allowing reverse-worded items to cross-load on the Prosocial subscale with, the exception of Ireland.…”
Section: Discussionsupporting
confidence: 78%
“…The respective models based on the three-factor structure with the correlated errors added, and with the reverse-worded items allowed to cross-load on the Prosocial dimension, displayed all of them lower fit indices than their correlated five-factor models. As so, the three-factor structure of the SDQ was found not adequate, similarly to the findings in previous studies [40,56,32,11]. Regarding this, ΔCFI analysis revealed that, contrary to van de Looij-Jansen et al [26], both in the three and the five-factor models, the inclusion of modifications is more significant in model fit than allowing reverse-worded items to cross-load on the Prosocial subscale with, the exception of Ireland.…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, the proportion of younger adolescents was higher in the Cluster related to Externalizing problems and lower prosocial capabilities, when compared with the older group. Previous studies have found contradictory results with regards to the age and the presentation of difficulties with the SDQ (Giannakopoulos et al, 2009;Koskelainen, Sourander, & Vauras, 2001;Rønning, Helge Handegaard, Sourander, & Mørch, 2004;Yao et al, 2009). However, other studies indicated similar results, with younger adolescents showing more Externalizing problems (Armand, Keypour, Maracy, & Attari, 2012;Lien, Green, Welander-Vatn, & Bjertness, 2009).…”
Section: Discussionmentioning
confidence: 36%
“…Tr anslated versions have been shown to function satisfactorily in Sweden (Smedje et al, 1999), Germany (Klasen et al, 2000), Bangladesh (Mullick and Goodman, 2001), the Gaza strip (Thabet et al, 2000) and Finland (Koskelainen et al, 2001). …”
Section: Use Of Measures In Child Psychiatric Researchmentioning
confidence: 96%